Design and Architectures for Digital Signal Processing - Ruiz, Gustavo; Michell, Juan A. (IntechOpen, 2013)
Digital signal processing (DSP) covers a wide range of applications in which the implementation of high-performance systems to meet stringent requirements and performance constraints is receiving increasing attention both in the industrial and academic contexts. Conceived to be available to a wide audience, the aim of this book is to provide students, researchers, engineers and the industrial community with a guide to the latest advances in emerging issues in the design and implementation of DSP systems for application-specific circuits and programmable devices. The book is divided into different sections including real-time audio applications, optical signal processing, image and video processing and advanced architectures and implementations. It will enable early-stage researchers and developers to deal with the important gap in knowledge in the transition from algorithm specification to the design of architectures for VLSI implementations.